Leadership Strategies in Building an Organizational Culture of Integrity to Maintain Domestic Security in the Era of Industrial Revolution 4.0 in Support of National Development - Indarto, Indarto (Pusat Publikasi Nusantara, 2024)
This study examines efforts to build a culture of integrity within the Indonesian National Police (Polri) through leadership strategies, strengthening organizational structure, and optimizing leadership processes. Data were collected through questionnaires distributed to 1,735 respondents, comprising both police officers and civilians, as well as through five rounds of Focus Group Discussions (FGDs). The qualitative approach involved in-depth interviews and FGDs to understand behaviors related to integrity and ethical leadership, while the quantitative approach was conducted through questionnaire distribution to civilians. The research findings indicate that the public's perceptions of integrity in Indonesia are in line with the perception of polri members. However, there is a significant percentage of respondents stated that their leaders have shown concern for ethical values, conveyed ethical standards, set an example in integrity behavior, and courageously admitted mistakes, but the results of FGD reveal a gap between rhetoric and practice, and a lack of consistency in integrity behaviors. This study contributes valuable perspectives on fostering integrity within law enforcement organizations, with implications potentially extendable to other contexts facing similar challenges.